Ruthenian Documents of the Chancery of Alexander Jagiellon, Grand Duke of Lithuania from a Paleographic Point of View - Jurkevičius, Andrius (Vilnius University Open Series, 2024)
The article examines paleographic specifics of Ruthenian documents of Alexander Jagiellon (1492–1506), Grand Duke of Lithuania. We looked into 17 documents of this ruler, kept in Lithuania and Poland. The examination of Alexander Jagiellon’s Ruthenian documents enabled us to establish the following: 1) the documents were written on two types of material – parchment or paper – using black or brown ink; 2) the documents were authenticated with pendant or applied seals of the Grand Duke of Lithuania, while other means of authentication such as signatures of the ruler or his officials were not detected; 3) individual letters in the texts of the documents are enlarged and/or decorated; 4) in all these documents, the slant of the letters varies (the letters are either vertical or slanted to the left or right); 5) some letters (mostly consonants) are raised above words, even though they make only a small part of all letters in the documents; 6) some words are made shorter by omitting vowels; 7) words are often (but not always) separated by spaces; 8) letters in individual words are almost never connected. The paleographic analysis of Alexander Jagiellon’s Ruthenian documents confirms an idea (expressed in historiography as early as in the last century) of the conditionality of the term “cursive” and manifestation of some traits of semi-uncial in Ruthenian documents of the Chancery of the Grand Duke of Lithuania in the 16th century. The Ruthenian documents of this ruler display features of both cursive and semi-uncial or even uncial. We also attempted to identify individuals (Alexander Jagiellon’s scribes) who could have been responsible for the preparation of documents and documents that could have been written by the same individual.
Keywords: Alexander Jagiellon; Ruthenian documents; paleography